How Numbers, Nature, and Immune Status of Foxp3+ Regulatory T-Cells Shape the Early Immunological Events in Tumor Development - Darrasse-Jeze, Guillaume; Podsypanina, Katrina (Frontiers in Immunology, 2013)
The influence of CD4+CD25+Foxp3+ regulatory T cells (Tregs) on cancer progression has been demonstrated in a large number of preclinical models and confirmed in several types of malignancies. Neoplastic processes trigger an increase of Treg numbers in draining lymph nodes, spleen, blood, and tumors, leading to the suppression of anti-tumor responses. Treg depletion before or early in tumor development may lead to complete tumor eradication and extends survival of mice and humans. However this strategy is ineffective in established tumors, highlighting the critical role of the early Treg-tumor encounters. In this review, after discussing old and new concepts of immunological tumor tolerance, we focus on the nature (thymus-derived vs. peripherally-derived) and status (naïve or activated / memory) of the regulatory T cells at tumor emergence. The recent discoveries in this field suggest that the activation status of Tregs and effector T cells (Teffs) at the first encounter with the tumor are essential to shape the fate and speed of the immune response across a variety of tumor models. The relative timing of activation/recruitment of antitumor cells versus tolerogenic cells at tumor emergence appears to be crucial in the identification of tumor cells as friend or foe, which has broad implications for the design of cancer immunotherapies.